Answer:
a) The amount of edging needed = 7.54 meters
b) Cost to edge the garden = $32.80
Step-by-step explanation:
a)
the amount of edging needed is basically the circumference (perimeter) of the circle. It has the formula:
[tex]C=2\pi r[/tex]
Where
C is the circumference
r is the radius
Given, diameter = 2.4, radius is HALF of it, so
r = 2.4/2 = 1.2
Now, finding circumference:
[tex]C=2\pi r\\C=2\pi (1.2)\\C=7.54[/tex]
The amount of edging needed = 7.54 meters
b)
$4.35 is needed to edge 1 meter, since we need 7.54 meters, we find the total cost by multiplying 4.35 with 7.54, so we have:
4.35*7.54 = $32.80
Cost to edge the garden = $32.80
What is the equation of a circle with center (1, -4) and radius 2?
A. (x-1)^2 + (y+4)^2 = 4
B. (x-1)^2 - (y+4)^2 = 4
C. (x-1)^2 + (y+4)^2 = 2
D. (x+1)^2 + (y-4)^2 = 4
Answer:
A) (x-1)^2+(y+4)^2=4
Step-by-step explanation:
Here's the equation of a circle with center and radius:
(x-h)^2+(y-k)^2=r^2 with the center being at the point (h, k)
and the radius being r.
(x-1)^2+(y-(-4))^2=2^2
(x-1)^2+(y+4)^2=4
The equation of a circle with center (1, -4) and radius 2 is (x-1)²+(y+4)²=4
The correct option is (A).
What is equation of circle?The equation of circle represents the locus of point whose distance from a fixed point is a constant value. This fixed point is called the center of the circle and the constant value is the radius of the circle.
The standard equation of circle with center at (x1,y1) and radius r is (x−x1)²+(y−y1)²=r².
We know equation of circle,
(x-a)²+(y-b)²=r²
Here, a=1, b=-4 and r=2
So,
(x-1)²+(y-(-4))²= 2²
(x-1)²+(y+4)²=4
Hence, the equation of circle is: (x-1)²+(y+4)²=4
Learn more about equation of circle here:
https://brainly.com/question/10618691
#SPJ5
what is the solution to the linear equation - 12 + 3B -1 = -5 - b
Step-by-step explanation:
3B+b=_5+12+1
4Bb=8
4Bb/4=8/4
Bb=2
Answer:
B = 2
Step-by-step explanation:
To solve the linear equation;
- 12 + 3B -1 = -5 - B
we will first collect like-term that is; we will make all the B variables to be on the left-hand side of the equation and all the constant to be on the right-hand side of the equation
( when -B cross over to the left-hand side of the equation, B becomes positive, when -12 and -1 cross over to the right-hand side of the equation, they become positive 12 and 1)
3B + B = -5 + 12 + 1
4B = 8
Divide both-side of the equation by 4 to get the value of B
4B/4 = 8/4
(on the left-hand side of the equation ,4 will cancel out 4 leaving us with B and 8 will be divided by 4 to give us 2)
B = 2
Therefore the solution to the linear of the equation is B = 2
Please help!!!!!!!! The question is in the picture!
Answer:
D
Step-by-step explanation:
multiply out the top to get 6x - 4 + 2x - 2 = 8x - 6
next look at the 4 choices.
when we multiply out and combine only for the x term, only the bottom two give us 8x.
3/4 * 4x + 5 * x = 8x
3/4 * 4x + 1/6 * 30x = 8x
next we look at the bottom two for which one will give us -6, in this case only D will.
3/4 * -8 + 5 * 15 = 69
3/4 * -12 + 1/6 * 18 = -6
What is the y intercept of the equation y=4x+1
Answer:
+1
Step-by-step explanation:
The y-intercept is +1.
You find a car that costs $18,500. If the interest rate on a 5-year loan is 6.25% and you make monthly payments on the car, what is the total amount of interest that you will pay over the life of the loan?
y-2=-(x+7) rewrite in standard form
Answer:
x + y = -5
Step-by-step explanation:
standard form is ax + by = c
equation is y - 2 = -x - 7
Add x to both sides.
x + y - 2 = -7
Now add 2 to both sides.
x + y = -5
Evaluate the expression when y = 4. 5 + y + 8
a.13
b.17
c.21
d.72
Answer:
17 is the simplified answer.
Step-by-step answer:
Given that:
y = 4.
We have to evaluate:
=5 + y + 8
By putting value of y that is y =4 in above equation:
=5 +4 +8
=9 +8
=17
So 17 is simplified answer for this question.
I hope it will help you!
801,504 round to the nearest thousand
Answer:
802,000
Step-by-step explanation:
The number in the thousands place is 1, and the number to the right of it is 5. And if the number to the right is greater than or equal to 5 the place value that you are rounding goes up by one.
Given 1+ cos x/ sin x + sin x/1+ cos x= 4, find a numerical value of one trigonometric function of x.
Answer:
The numerical value of the trigonometric function is 30 °
Step-by-step explanation:
Given trigonometric function as :
[tex]\frac{1 + cos x}{sin x}[/tex] + [tex]\frac{sin x}{1 + cos x}[/tex] = 4
or, Taking LCM we get
[tex]\frac{(1+cosx)^{2}+sin^{2}x}{(sinx)\times (1+cosx)}[/tex] = 4
Or, ( 1 + cos x )² + sin² x = 4 × ( sin x ) × ( 1 + cos x )
1 + cos² x + 2 cox + sin² x = 4 sin x + 4 sin x × cos x
or, ( cos² x + sin² x ) + ( 1 + 2 cos x ) = 4 sin x ( 1 + cos x )
∵ cos² x + sin² x = 1
or, 1 + 1 + 2 cos x = 4 sin x ( 1 + cos x )
or, 2 + 2 cos x = 4 sin x ( 1 + cos x )
or, 2 ( 1 + cos x ) = 4 sin x ( 1 + cos x )
Or, [tex]\frac{2 ( 1+ cos x )}{4 ( 1 + cos x )}[/tex] = sin x
Or, sin x = [tex]\frac{1}{2}[/tex]
∴ x = [tex]sin^{-1}\frac{1}{2}[/tex]
∵ sin 30 ° = [tex]\frac{1}{2}[/tex]
I.e x = 30 °
Hence The numerical value of the trigonometric function is 30 ° answer
Answer: D. sin x= 1/2
Step-by-step explanation:
Edg 2020
Paula used these steps to solve an equation:
Step 1: -4(7 + 8) - 21 = 25
Step 2: -4r – 32 - 2x = 25
Step 3: -61 – 32 = 25
Step 4: -6x = 57
Step 5: x = -95
Between which two steps did Paula use the division property of equality?
Answer:
Between step 4 and step 5
Step-by-step explanation:
The Division Property of Equality states that when both sides of an equation are divided by the same nonzero number, both sides remain equal.
That is, if a, b, and c are real numbers such that a = b and c ≠0, then
[tex]\frac{a}{c} = \frac{b}{c}[/tex]
At step 4: The equation was -6x = 57
To move to step 5, Paula had to divide both sides by the co-efficient of x (-6) in order to get the value of x. See below
[tex]-6x = 57[/tex] ---- Divide both sides by -6 (Step 4)
[tex]\frac{-6x}{-6} = \frac{57}{-6}[/tex] ---- (Intermediary between step 4 and 5)
[tex]x = -9.5[/tex] ----- Step 5
Hence, we can conclude that the division property of equality was done between step 4 and step 5
A park ranger calculated that 60% of the deer they tagged were male. Of the male deer that
were tagged, 20% of them were older than 4 years. They tagged 18 male deer that were
older than 4 years. How many deer did they tag?
A
45
Answer:
They tagged 90 male deer s
Explanation:
Given a park ranger calculated 60% of male deer
Consider the deer they tagged to be x
According to question,
20% of deer were older than 4 years which equals 18
Then, 20% of x = 18
Solving for x,
x = 1800/20
x = 90
So, they tagged 90 male deer
the formula d = 26t + 32.5 can be used to find the distance (d) between two cars after traveling (t) hours in opposite directions. How many hours will it take for the cars to be 117 miles apart?
A: 0.5
B: 2.05
C: 3.25
D: 4.5
Answer:
C
Step-by-step explanation:
The formula given is:
[tex]d=26t+32.5[/tex]
Where
d is the distance between two cars
and
t is the time it takes
We want the time it takes (so we need t) for the cars to be 117 miles apart (this is the distance). Thus, it means:
d = 117
t = ???
We plug in 117 into d and solve the equation for t. Shown below:
[tex]d=26t+32.5\\117=26t+32.5\\117-32.5=26t\\84.5=26t\\t=\frac{84.5}{26}\\t=3.25[/tex]
So, it takes 3.25 hours
Correct answer is C
Final answer:
Using the formula d = 26t + 32.5 and setting d to 117 miles, we solve for t to find that it takes approximately 3.25 hours for the two cars to be 117 miles apart. The correct answer is C: 3.25.
Explanation:
To find out how many hours it will take for two cars to be 117 miles apart if they travel in opposite directions using the formula d = 26t + 32.5, we need to set d equal to 117 miles and solve for t.
First, we substitute 117 for d in the equation:
117 = 26t + 32.5
Next, we subtract 32.5 from both sides to isolate the term with t:
117 - 32.5 = 26t => 84.5 = 26t
Then we divide both sides by 26 to solve for t:
t = 84.5 / 26 => t ≈ 3.25
Hence, it will take approximately 3.25 hours for the cars to be 117 miles apart.
Thus, the correct answer is C: 3.25.
Mia ordered five DVDs, all at the same price, from an online retailer. There was a shipping charge of $14.50 for the complete order but no sales tax. If Mia’s total charge for her order was $79.45, what was the price of each DVD?
Answer:
$12.99
Step-by-step explanation:
you take $79.45 and subtract it by $14.59 that equals $64.95. Then you take 64.95 and divide it by 5 and your total of each DVD is 12.99
The price of each DVD from online retailer is, $12.99
What is mean by Subtraction?Subtraction in mathematics means that is taking something away from a group or number of objects. When you subtract, what is left in the group becomes less.
We have to given that;
There was a shipping charge of $14.50 for the complete order but no sales tax.
And, Mia’s total charge for her order was $79.45.
Now, The cost of 5 DVD = $79.45 - $14.50
= $64.95
Hence, The price of each DVD from online retailer is,
⇒ $64.95 / 5
⇒ $12.99
Learn more about the subtraction visit:
https://brainly.com/question/17301989
#SPJ2
It takes 12 hours for 7 men to paint a room.
How many men would be needed to paint the room in 3 hours?
28 men are needed to paint the room in 3 hours
Solution:Given that it takes 12 hours for 7 men to paint a room
We are asked to find number of men required to paint the room in 3 hours
Recognize, "paint the room" is 1 task. One job.
7 men -------- 12 hours ------ 1 job
(7/7) = 1 men ------- 12 x 7 (84) ------- same 1 job
The one men is rate is 84 hours to do the job
We can express this as 1/84 jobs per hour, the one-person rate
Now lets find how many men needed to paint the room in 3 hours
Let the required number of men for 3 hours be "a"
The rates of each person is simply additive.
[tex]a \times \frac{1}{84} \times 3 = 1[/tex]
corresponds to rate x hours = jobs and "a" is a variable for how many men
[tex]a \times \frac{1}{28} = 28[/tex]
Thus 28 men are needed to paint the room in 3 hours
If an account is increasing at a rate of 3.3% compounded semiannually, what is the exact value of in the following present value
ordinary annuity formula?
PV-P1-(1+1)*
a) 3.3
b) 0.033/100
c) 0.033/2
d) 0.33/2
Answer:
The correct answer is C. 0.033/2
Step-by-step explanation:
1. Let's review the data given to us for solving the question:
Annual interest rate = 3.3% compounded semiannually
2. Let's find the exact value of the rate:
Number of periods (n) = n/2, given that periods are semesters and not years
Annual interest rate (r) = 3.3% = 3.3/ 100 = 0.033
For using the correct value in the present value annuity formula, we also have to divide the annual interest rate because the interest is compounded semiannually or every six months, what it means:
0.033/2
The correct answer is C. 0.033/2
c. [tex]\frac{0.033}{2}[/tex]
on edgen
Basketball star Mumford (a six foot senior forward) places a mirror on the ground x ft. from the base of a basketball goal. He walks backward four feet until he can see the top of the goal, which he knows is 10 feet tall. Determine the how far the mirror is from the basketball goal. Justify your answer.
will give 5 stars and mark brainliest.
Answer:
6.67 feet
Step-by-step explanation:
The situation is as shown in the figure.
ON is the normal to the mirror at the point of incidence O
⇒ ∠BON = ∠DON = 90°
By the laws of reflection: angle of incidence = angle of reflection :
∠AON = ∠CON
⇒ ∠AOB = ∠COD
⇒tan(∠AOB) = tan(∠COD)
⇒[tex]\frac{AB}{OB}[/tex] = [tex]\frac{CD}{OD}[/tex]
⇒[tex]\frac{6}{4}[/tex] = [tex]\frac{10}{x}[/tex]
⇒x = [tex]\frac{40}{6}[/tex] = [tex]\frac{20}{3}[/tex] = 6.67 ft
∴ Distance of the mirror from basketball goal is 6.67 ft
Final answer:
Using the principles of similar triangles, we determine that the mirror is 6 feet from the basketball goal by setting up a proportion between the heights and distances of the triangles formed by the goal and Mumford's line of sight. The mirror is 6 feet from the basketball goal.
Explanation:
To determine how far the mirror is from the basketball goal, we can use the principles of similar triangles. Basketball star Mumford is a six-foot-tall senior forward, meaning he is 6 feet above the ground. The basketball goal is 10 feet tall. If he walks backward four feet, and then he is able to see the top of the basketball goal, we can set up a proportion because the angles of incidence and reflection are equal.
Let's let x be the distance from the base of the basketball goal to the mirror. We then have two similar triangles to work with:
The large triangle with the height of the goal (10 feet) and the base x + 4 feet (distance from the goal to Mumford's eyes).
The smaller triangle with the height from Mumford's eyes to the ground (which is 6 feet because he's a six-foot-tall person) and the base x (distance from the goal to the mirror).
The proportion we set up is:
(Height of basketball goal) / (Distance from goal to Mumford's eyes) = (Height of Mumford's eyes from the ground) / (Distance from goal to the mirror)
10 / (x + 4) = 6 / x
Solving for x gives us the distance from the mirror to the basketball goal:
10x = 6(x + 4)
10x = 6x + 24
4x =24
x = 6
Therefore, the mirror is 6 feet from the basketball goal.
5a(-3b)(-2a^2b^3)
what is the answer to this question?
Answer:
(3•5•2a3b4)
Step-by-step explanation:
Step by step solution :
Step 1 :
Equation at the end of step 1 :
-15ab • (0 - (2a2 • b3))
Step 2 :
Multiplying exponential expressions :
2.1 a1 multiplied by a2 = a(1 + 2) = a3
Multiplying exponential expressions :
2.2 b1 multiplied by b3 = b(1 + 3) = b4
i will give brainliest
Which expression represents the sequence below?
16, 24, 32, 40.....
an=4n+1 an=8n+8 an=8n+16
Answer:
[tex]a_n = 8n+8[/tex] represent the sequence 16,24,32,40...
Step-by-step explanation:
The sequence given is
16,24,32,40.
And the options given are
an=4n+1
an=8n+8
an=8n+16
We will check for all so as to find the correct expression.
In the given sequence the first term is 16,
i.e a1 = 16
1). We will check for an = 4n+1 whether the first term is 16 or not.
We will put the value of n as 1;
[tex]a_1= 4\times1+1= 4+1=5[/tex]
With this option we get the first term as 5 but in the given sequence first term is 16.
Hence this option is Incorrect.
2). We will check for an = 8n+8 whether the first term is 16 or not.
We will put the value of n as 1;
[tex]a_1= 8\times1+8= 8+8=16[/tex]
With this option we get the first term as 16 and in the given sequence also first term is 16.
Hence this option is correct.
3). We will check for an = 8n+16 whether the first term is 16 or not.
We will put the value of n as 1;
[tex]a_1= 8\times1+16= 8+16=24[/tex]
With this option we get the first term as 24 but in the given sequence first term is 16.
Hence this option is Incorrect.
Hence we can say that an = 8n+8 represent the sequence 16,24,32,40...
please solve much appreciated
Answer:
i) C; x=y= 80°, ii) B; x= 58°, iii) D; x= 62° and y= 56°, iv) D; none of these are correct.
Step-by-step explanation:
i) Full angle around is 360°
As given one angle is 100°,which means vertically opposite angles are equal to 100°
Now, remaining angle is equal to [tex]360-200= 160°[/tex]
∵ x and y are vertically opposite angle, which means they are equal.
∴x=y= 80°
ii) As we know straight angle is equal 180°
As given one of the angle is 32° and other says, it is a right angle which is equal to 90°.
∴ ∠x= [tex]180-(90+32)= 58°[/tex]
∴∠x= 58°
iii) Full angle = 360°
2∠x = 124° (∵ Vertically opposite angle are equal )
⇒∠x= [tex]\frac{124}{2}[/tex]
∴∠x= 62°
∠x+∠x+∠y= 180° (∵ it is a straight angle)
2∠x+∠y= 180°
⇒[tex]124+ y= 180[/tex]
Subtracting both side by 124
⇒∠y= [tex]180-124= 56°[/tex]
∴∠y= 56°
iv) Full angle= 360°
∴ ∠x+22°+32°+51°= 360°
Subtracting both side by 105
∠x= [tex]360-105= 255°[/tex]
∴∠x= 255°
Which means none of the given option are correct.
What is the following product? Square root y^3 * square root x^3
The product of two square roots is equal to the square root of the product, so the product of √y3 and √y3 is y3.
The equation is asking you to multiply the square root of y cubed by itself.
Based on the properties of square roots, if you multiply the square root of a number by itself, you get the original number.
This is because multiplication is the inverse operation for square roots. Meaning, it undoes the square root.
So, in this scenario, you are multiplying [tex]\sqrt{y^{3} }[/tex] * [tex]\sqrt{y^{3} }[/tex]which results in y^3.
Thus, the product of [tex]\sqrt{y^{3} }[/tex] and [tex]\sqrt{y^{3} }[/tex]is y^3, assuming y≥0.
Learn more about Square Roots here:
https://brainly.com/question/3120622
#SPJ2
10 students per teacher. Write two ratios to represent this information
I need to write an equation for y = mx + b, The numbers i have are 20-80 and 1-4
Answer:
y = 20x
m = 20 and b = 0
Step-by-step explanation:
For input values of x = 1, output value of y = 20 and for x = 4, y = 80.
Therefore, the equation of this relation can be written as
[tex]\frac{y - 80}{80 - 20} = \frac{x - 4}{4 - 1}[/tex]
⇒ 3(y - 80) = 60(x - 4)
⇒ 3y - 240 = 60x - 240
⇒ y = 20x
Now, y = mx + b is the equation and hence, m = 20 and b = 0 and the actual equation is y = 20x. (Answer)
5,069 round to the nearest tenth
Answer:
5,070
Step-by-step explanation:
Answer:
5069.0
Step-by-step explanation:
The tenth value is the value directly after the decimal point. In this case, the number given is a whole number, and so to find the tenth place value, add a decimal point and a 0 to the back.
~
x/5 +8=3 what would x be
Answer: x= -25
Step-by-step explanation:
Answer:
x=-25
Step-by-step explanation:
x/5 = 8 = 3 you would multiply both sides by 5
youd end up with x+40=15 then you would move the constan to the right
x=15-40 you would subtract 40 from 15
x=-25
A movie theater has a seating capacity of 187. The theater charges $5.00
for children, $7.00 for students, and $12.00 of adults. There are half as
many adults as there are children. If the total ticket sales was $ 1356, How
many children, students, and adults attended?
There were 69 children, 83.5 students, and 34.5 adults in attendance at the movie theater.
Explanation:To solve this problem, we can set up a system of equations.
Let's denote the number of children as 'c', the number of students as 's', and the number of adults as 'a'.
From the given information, we have the following equations:
c + s + a = 187 (equation 1)
5c + 7s + 12a = 1356 (equation 2)
We also know that there are half as many adults as children, so we have the equation:
a = (1/2)c (equation 3)
Substituting equation 3 into equations 1 and 2, we can solve for the variables.
Substituting (1/2)c for a in equation 1:
c + s + (1/2)c = 187
(3/2)c + s = 187 (equation 4)
Substituting (1/2)c for a in equation 2:
5c + 7s + 12((1/2)c) = 1356
5c + 7s + 6c = 1356
11c + 7s = 1356 (equation 5)
Now we can solve equations 4 and 5 simultaneously:
Multiplying equation 4 by 11:
(33/2)c + 11s = 2057/2
11c + 7s = 1356
Subtracting the second equation from the first:
(33/2)c - 11c = 2057/2 - 1356
(-1/2)c = -69/2
c = 69
Substituting c = 69 into equation 4:
(3/2)(69) + s = 187
103.5 + s = 187
s = 83.5
Finally, substituting c = 69 and s = 83.5 into equation 3:
a = (1/2)(69)
a = 34.5
Therefore, there were 69 children, 83.5 students (which is not a whole number, so it could be rounded to 84 students), and 34.5 adults (which could be rounded to 35 adults) in attendance at the movie theater.
4. A home purchased for $120,000 in 2012 is sold for $156,000 in 2015. What is the percent
change in the price?
i need help with 7-10 plz help
Answer:
bro in Ur pictures there is no 7-10
Step-by-step explanation:
10-7 is 3 right so 7-10 is -3 it simple . but show me questions again because there is no 7-10 . Thank for ur asking me !
2x - (4x - 4) = 16 - 8
What is the answer
Answer:
X=-2
Step-by-step explanation:
PLUG IT IN HTE EQUATION BRAINLIEST PLZZZ
Answer:
x = - 2
Step-by-step explanation:
Given
2x - (4x - 4) = 16 - 8 = 8 ← distribute parenthesis and simplify left side
2x - 4x + 4 = 8
- 2x + 4 = 8 ( subtract 4 from both sides )
- 2x = 4 ( divide both sides by - 2 )
x = - 2
Through:(5,1), parallel to y =1/5x-4
If the line is parallel to y=1/5x-4, the line must have the same slope.
So, the slope of your line is 1/5.
Now we need to find the y intercept. We should use the point given.
y=mx+b
1=1/5(5)+b
b=0
Equation: y=1/5x
Answer:
y = (1/5)x
Step-by-step explanation:
y = mx+b
m= slope would be the same i.e. 1/5 , since it's parallel to the given equation.
y= 1
x= 5
Hence, let's look for the equation of this line of which the coordinate is provided!
1 = (1/5)(5) + b
1 = 1 +b
1-1 = b
b = 0
Hence the equation of this line is:
y = 1/5(x)
Hope this helps!
Mark brainliest of you think I helped! Would really appreciate!
please explain, but not to wordy
Solving the expression [tex]\frac{x^2-12x+32}{x^2-10x+16}.\frac{6x-30}{25-5x}[/tex] we get [tex]-\frac{6(x-4)}{5(x-2)}[/tex]
Step-by-step explanation:
Solving the expression:
[tex]\frac{x^2-12x+32}{x^2-10x+16}.\frac{6x-30}{25-5x}[/tex]
Solving the expression:
We will find factors of the quadratic terms:
[tex]x^2-12x+32\\=x^2-8x-4x+32\\=x(x-8)-4(x-8)\\=(x-4)(x-8)[/tex]
So, factors of [tex]x^2-12x+32[/tex] are [tex](x-4)(x-8)[/tex]
[tex]x^2-10x+16\\=x^2-8x-2x+16\\=x(x-8)-2(x-8)\\=(x-2)(x-8)[/tex]
So, factors of [tex]x^2-10x+16[/tex] are [tex](x-2)(x-8)[/tex]
Placing factors instead of quadratic equation and finding common terms:
[tex]\frac{(x-4)(x-8)}{(x-2)(x-8)}.\frac{6(x-5)}{-5(x-5)}[/tex]
Cancelling the common terms:
[tex]\frac{(x-4)}{(x-2)}.\frac{6}{-5}\\-\frac{6(x-4)}{5(x-2)}[/tex]
So, Solving the expression [tex]\frac{x^2-12x+32}{x^2-10x+16}.\frac{6x-30}{25-5x}[/tex] we get [tex]-\frac{6(x-4)}{5(x-2)}[/tex]
Keywords: Solving Fractions
Learn more about Solving Fractions at:
brainly.com/question/2456302 brainly.com/question/4390083 brainly.com/question/2456302#learnwithBrainly